2015
DOI: 10.1111/jcmm.12614
|View full text |Cite
|
Sign up to set email alerts
|

GFAP and antibodies against NMDA receptor subunit NR2 as biomarkers for acute cerebrovascular diseases

Abstract: We studied whether the serum levels of glial fibrillary acidic protein (GFAP) and of antibodies against the N-methyl-d-aspartate receptor subunit NR2 (NR2 RNMDA) can discriminate between intracerebral haemorrhage (ICH) and ischaemic stroke (IS) in stroke patients. We prospectively recruited patients with suspected stroke (72 confirmed) and 52 healthy controls. The type of brain lesion (ICH or IS) was established using brain imaging. The levels of GFAP and of antibodies against NR2 RNMDA were measured in blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 31 publications
1
14
0
3
Order By: Relevance
“…Our results are partially in accordance with the findings of Foerch et al [15] and Stanca et al [29] . However, sensitivity in our cohort was lower than that reported by their evaluation (36% compared to 84 and 94%, respectively).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are partially in accordance with the findings of Foerch et al [15] and Stanca et al [29] . However, sensitivity in our cohort was lower than that reported by their evaluation (36% compared to 84 and 94%, respectively).…”
Section: Discussionsupporting
confidence: 83%
“…The results suggest that achieving higher levels of sensitivity in detection of ICH in a very early time window may require additional biomarker or clinical information. This approach was recently investigated by Stanca et al [29] who added the assessment of antibodies against NMDA receptor subunit NR2 to GFAP and found a sensitivity of 94% and specificity of 91% for discrimination between ischemic and hemorrhagic stroke. However, the 2 biomarkers were taken at 12 h after stroke, which is clearly too late for making treatment decisions in the hyperacute phase.…”
Section: Discussionmentioning
confidence: 99%
“…We included 11 studies involving 1297 participants (350 with ICH and 947 with either AIS or mimic). [10][11][12][13][21][22][23][24][25][26][27] The sensitivity and specificity reported in included studies ranged from 0.36 (95% CI 0.18-0.57) to 0.96 (95% CI 0.78-1.00) and 0.64 (95% CI 0.53-0.74) to 1.00 (95% CI 0.93-1.00), respectively (Figure 2(a)). Information on type of GFAP assay, minimum detectable concentration of GFAP, whether positivity thresholds were pre-defined, and risk of bias were available; other pre-defined covariates were either not reported or reported heterogeneously and were therefore not included in the meta-regression.…”
Section: Search Resultsmentioning
confidence: 99%
“…[ 47 ] Furthermore, a recent study suggested that GFAP used in combination with NR2 can differentiate between ischemic stroke and ICH at a time point extended to 12 h after the ictus with a sensitivity of 94% and specificity of 91%. [ 46 ] Another study showed that plasma concentrations of retinol binding protein 4 and GFAP at concentrations >61 μg/mL and <0.07 ng/mL, respectively, demonstrated 100% specificity, and these biomarkers might be independent predictors to discriminate stroke subtype, improving discrimination by 29% ( P < 0.0001). [ 48 ]…”
Section: Use Of Blood Glial Fibrillary Acidic Protein Levels For Earlmentioning
confidence: 99%